Factors Affecting Career Selection as a Public Accountant - Zidni Husnia Fachrunnisa; Vivi Artiningtyas; Anandita Zulia Putri (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2022)
This study aims to determine whether financial rewards, labor market considerations, family environment, professional recognition, and work environment have a positive effect on student interest in choosing a career as a public accountant. The population in this study is students at the University in the Special Region of Yogyakarta. The sampling method used is purposive sampling. This research is study quantitative data with primary data obtained by distributing questionnaires through google forms. The total number of samples is 100 students. A multiple linear regression analysis was used to analyze the influence of financial rewards, labor market considerations, family environment, professional recognition, and work environment on student interest in choosing a career as a public accountant. The results showed that financial rewards and family environment did not affect the students' interest in choosing a career as a public accountant. Meanwhile, labor market considerations, professional recognition, and work environment have a positive and significant impact on students' interest in choosing a career as a public accountant. The implication of the results of this study that is the Indonesia Public Accountants Associate (IAPI) can give more many information related to the profession of a public accountant to the student. In addition, IAPI as a regulator is expected could guard auditor professionalism so that increase the perception of students in accounting majors about profession public accountants. That thing expected could increase the interest of accounting students in choosing a career as a public accountant.